A 5‐Year Longitudinal Study on Mood Variability Across Adolescence Using Daily Diaries. Issue 6 (14th October 2015) - Maciejewski, Dominique F.; van Lier, Pol A. C.; Branje, Susan J. T.; Meeus, Wim H. J.; Koot, Hans M.
Abstract : This study explored the development of mood variability in 474 Dutch adolescents (56.8% male, 90.1% medium to high socioeconomic status) from a community sample, followed from ages 13 to 18 years. Three times per year, adolescents reported on daily happiness, anger, sadness, and anxiety for 5 days using Internet diaries (15 assessment weeks; from 2006 to 2010). Mood variability scores were calculated as means of absolute differences between consecutive days. Results showed that happiness, anger, and sadness variability continuously declined across adolescence, while anxiety variability increased initially, then decreased, and then increased toward late adolescence. Despite females experiencing higher happiness and sadness variability, the rate of change across adolescence was similar for both sexes. Implications for normative emotional development and future studies are discussed.